Determinants of Pet-Friendly Tourism Behavior: An Empirical Analysis from Chile - Escobar-Farfan, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Pet tourism has experienced significant growth in recent years, reflecting changes in the perception of pets as family members. This research examines the factors influencing attitude, travel intention, and payment intention in pet tourism in Chile, specifically analyzing the role of emotional attachment, perceived benefits, prestige, and novelty. Using a quantitative methodology, data were collected through an online survey of pet owners in Chile. The results reveal that perceived benefits and novelty positively influence attitudes toward traveling with pets, while prestige and perceived benefits directly impact travel intention. Surprisingly, emotional attachment did not show a significant influence, which contrasts with previous studies in other cultural contexts. This research also confirms that attitude and travel intention are relevant predictors of willingness to pay more for pet-friendly tourism services. These findings contribute to the literature on pet tourism in Latin America and provide practical implications for developing tourism services tailored to the Chilean market. This study concludes that marketing strategies in the tourism sector should emphasize tangible benefits and novel elements rather than emotional aspects to attract this growing market segment. © 2025 by the authors.